Environmental impacts of fast fashion: the international textile dump of Atacama - Chile - Ferreira Costa, Mila Fonteles Barbosa; Bruno Bacellar Zaneti, Izabel Cristina Bruno [UNESP] (Univ Tecnologica Fed Parana-utfpr, 2022)
The phenomenon of democratization of fashion has fueled an unsustainable chain of consumption, which ends up turning into garbage in a short period of time. This same waste, difficult to recycle due to high costs and synthetic materials, causes environmental and social damage. The Atacama Desert, in Chile, is home to an open-air clothing cemetery, as a result of the activity of the Free Zone at the port of Iquique. The present study aims to identify the main factors that contribute to the fact that the Atacama Desert, in Chile, is home to one of the largest textile dumps on the planet. The specific objectives are: to present the commercial processes that leave textile waste in the port of Iquique and the reasons that lead local management to not send textile waste to recycling processes; report the main environmental impacts caused by the Atacama textile dump, in Chile. The methodological procedures used were bibliographic and literature reviews, with content analysis under the qualitative bias and creation of an infographic for a better understanding of the processes aligned with the constitution of the Atacama textile dump. It is concluded that the lack of appropriate legislation and inspection by the authorities linked to the environment contribute to the unsustainability of this situation in Chile.
Keywords: Fast fashion textile waste; Atacama; Sustainability